(untitled) (Journal of Economics and Management Research, 2023)
تهدف هذه الورقة البحثية الى دراسة دور تقنية سلسلة الكتل في تعزيز الشمول المالي، وشرح تطبيقات سلسلة الكتل التي يمكن استخدامها لتوسيع الشمول المالي. وتوصلنا إلى أن تطبيق سلسلة الكتل والعقود الذكية في الخدمات المالية يمكنه تعزيز الشمول المالي، وذلك لقدرتها على تحسين رضا العملاء وتوفير مختلف الخدمات المالية الملائمة، وتقليل التكاليف ورسوم التحويلات والمدفوعات المالية، زيادة على ذلك قدرتها على الوصول إلى المستبعدين ماليا وتوفير حسابات وهويات رقمية آمنة. This research paper aims to study the role of the application of block chain technology in promoting financial inclusion, and to explain the applications of block chain that can be used to expand financial inclusion. We found that the application of blockchain and smart contracts in financial services can enhance financial inclusion, due to its ability to improve customer satisfaction, provide various appropriate financial services, reduce costs and fees for transfers and financial payments, in addition to its ability to reach the financially excluded and provide secure digital accounts and identities.